What useful can be a virtual world like Second Life and the augmented reality? - Tosete, Francisco (Anuario ThinkEPI, 2009)
Until now, the paradigm of Human-Computer Interaction has focused on the interaction with two-dimensional interfaces showing the strong dichotomy between the real and the digital. The advent of virtual worlds are opening up new possibilities to develop spaces that can be more appropriate in certain circumstances to show users specific type of information, create physical places or objects which faithfully represent the real world, geolocate or interact with them beyond the limitations of twodimensional images and the written word. Finally, the arrival of the augmented reality aims to go beyond the simulation of a three-dimensional environment on a flat surface such as a monitor showing the three-dimensional virtual objects and take all the digital advantages resulting from this for improve the learning and knowledge human.